The Carboniferous onset of subduction at SW Gondwana revisited: Sedimentation and deformation processes along the late Paleozoic forearc of north Chile (21°–33° S). (April 2021) - Creixell, Christian; Sepúlveda, Fernando; Álvarez, Javier; Vásquez, Paulina; Velásquez, Ricardo
Abstract: The geological record of late Paleozoic rocks is ubiquitous along the north to central Chile (21°–33° S). The most accepted evolutionary model proposes that the SW-Gondwana margin in northern Chile (north of 28° S) evolved from a passive margin setting in the Devonian to late Carboniferous that switched to an active margin setting during the early to late Carboniferous and continued during the Permian. South of 28° S, the accretion of an allochtonous terrane (Chilenia) took place during the mid or late Devonian and during the Carboniferous subduction was renewed along the western margin of the accreted terrane. In light of a large amount of new data recently published for Paleozoic rocks between 21° and 33° S, we evaluate these models in order to understand the geodynamic processes that lead to the formation of the late Paleozoic active margin (Gondwanan Orogenic cycle) and attempt to decipher processes that controlled subduction initiation during those times. Our data compilation and subsequent analysis allow us to establish that Gondwanan magmatism started ca. 331 Ma around 29°–31° S, and the onset of subduction probably took place around 340 to 345 Ma. These data also allow establishing that the Gondwanan active margin was segmented along the study area, with a northern part affected by extension, probably under the influence of a thermal anomaly that led to the emplacement of forearc migmatites during the late Carboniferous (Caleta Loa Metamorphic Complex). We propose that subduction renewal during the early Carboniferous started around 29°–31° S, in an area close to the northern limit of the previously accreted Chilenia terrane, and was induced by plate forces, but probably also influenced by mechanical heterogeneities along the continental and the oceanic plates at that point. Highlights: Continuous sedimentation occurred along the SW-Gondwana margin between the Devonian and the late Carboniferous. The Gondwanan orogenesis had active subduction starting from the early Carboniferous (340–345 Ma). The Gondwanan margin was segmented in north Chile, with its northern part affected by a thermal anomaly and extension. Subduction-related magmatism in north-central Chile started at ca. 331 Ma. The onset of Gondwanan subduction took place south of 28°S (ca. 29°-31° S) and then was propagated to north and south.